2(2b+1)-6x=4

Simple and best practice solution for 2(2b+1)-6x=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2b+1)-6x=4 equation:


Simplifying
2(2b + 1) + -6x = 4

Reorder the terms:
2(1 + 2b) + -6x = 4
(1 * 2 + 2b * 2) + -6x = 4
(2 + 4b) + -6x = 4

Solving
2 + 4b + -6x = 4

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + 4b + -2 + -6x = 4 + -2

Reorder the terms:
2 + -2 + 4b + -6x = 4 + -2

Combine like terms: 2 + -2 = 0
0 + 4b + -6x = 4 + -2
4b + -6x = 4 + -2

Combine like terms: 4 + -2 = 2
4b + -6x = 2

Add '6x' to each side of the equation.
4b + -6x + 6x = 2 + 6x

Combine like terms: -6x + 6x = 0
4b + 0 = 2 + 6x
4b = 2 + 6x

Divide each side by '4'.
b = 0.5 + 1.5x

Simplifying
b = 0.5 + 1.5x

See similar equations:

| -4(x+15)=28 | | 7x-3x-14=14 | | 5+33=158 | | 4(a-5)=30 | | -18x+2y^2=0 | | x-5=2x+x+6 | | X^2/(.2-x)=7.54 | | x-2=5(x-6) | | x-5=2x-x+6 | | x-2=(x-6) | | 10=7t+-12t | | 3/5*1/3*4/7 | | -3x+.7=-x-.3 | | .25(5x+11)=19 | | x=81+5x | | x+4+3x=-20 | | 7(x-1)+x=36 | | 1x+4+3x=-20 | | 2/3(n-6=5n-43 | | (2q+1)-(3d+1)= | | X+3x-4=8 | | (2x-1)(8x+1)=0 | | 2x+x+2=8 | | 5e+2e=10 | | x=-2*4/3 | | 3y+8=4y-2 | | f(x)=2x^2+7x-15 | | 22x-4=40forx | | 2x-(x+8)=11x-7(2x-8)+2 | | 5x+7x=15 | | 500(1-(x/90))^2 | | M^2-7m-11/m-8 |

Equations solver categories